2014
DOI: 10.1158/0008-5472.can-14-1592
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor of Activated T-cell Activity Is Associated with Metastatic Capacity in Colon Cancer

Abstract: Metastatic recurrence is the leading cause of cancer death in patients with colorectal carcinoma. In order to capture the molecular underpinnings for metastasis and tumor progression, we performed integrative network analysis on 11 independent human colorectal cancer gene expression data sets and applied expression data from an immunocompetent mouse model of metastasis as an additional filter for this biological process. In silico analysis of one metastasis-related co-expression module predicted Nuclear Factor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 36 publications
(42 reference statements)
3
85
0
Order By: Relevance
“…We only included positive correlations in our analysis because we found that a strong negative correlation between two genes did not necessarily correspond to high functional similarity between the genes (supplemental Fig. S1), which is consistent with previous reports (36, 37). …”
Section: Methodssupporting
confidence: 81%
“…We only included positive correlations in our analysis because we found that a strong negative correlation between two genes did not necessarily correspond to high functional similarity between the genes (supplemental Fig. S1), which is consistent with previous reports (36, 37). …”
Section: Methodssupporting
confidence: 81%
“…It has been demonstrated that the sustained activity of NFAT2 is able to induce transformation hallmarks (Fig. 2) (9,49) and is linked to some malignant transformations, such as Burkitt lymphoma, DLBCL, T-cell acute lymphoblastic leukemia ((T-ALL), CLL, melanoma, and pancreatic and colorectal carcinomas (11,(20)(21)(22)(23)50). NFAT2 also regulates genes important for tumorigenesis and tumor development, including those for c-myc, BLyS, and Cox-2 (11,(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the oncogenic potential of the NFAT family member NFAT2. NFAT2 was fundamental for pancreatic cancer progression and contributed to the survival of melanoma cells and the metastatic potential of colorectal cancer cells (11,20,21). Furthermore, NFAT2 was activated in 70% of Burkitt lymphoma cases and in ϳ30% of diffuse large B cell lymphoma (DLBCL) cases and was overexpressed and activated in cases of chronic lymphocytic leukemia (CLL) (22,23).…”
mentioning
confidence: 99%
“…Additional supplements were added in the growth medium for YAMC cells as previously described (20). The integrity of cell lines used in this study is described in our recent publications (21). The patient-derived xenograft line, CR-IGR-0034P, was purchased from Oncodesign, France.…”
Section: Methodsmentioning
confidence: 99%